1997
DOI: 10.1016/s0022-5347(01)64113-2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence and Lower Urinary Tract Symptoms: An Epidemiological Study of Men Aged 45 to 99 Years

Abstract: The prevalence of urinary incontinence and lower urogenital tract symptoms, such as hesitancy, weak stream, dribbling, sensation of incompletely emptied bladder, nocturia, urinary tract infection and impotence, increased linearly with increasing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
1
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(95 citation statements)
references
References 18 publications
10
78
1
6
Order By: Relevance
“…Studies that have investigated nocturia have varied in their de¢nitions of the condition and its surrounding terminology, and these discrepancies have been highlighted in the literature Weiss & Blaivas, 2000;van Kerrebroeck & Weiss, 1999]. However it is de¢ned, prevalence studies show that nocturia is reported to be a very common condition, a¡ecting particularly older age groups [Chute, 1993;Malmsten, 1997;Swithinbank, 1998]. …”
Section: (International Continence Society De¢nition From Ics Standarmentioning
confidence: 99%
“…Studies that have investigated nocturia have varied in their de¢nitions of the condition and its surrounding terminology, and these discrepancies have been highlighted in the literature Weiss & Blaivas, 2000;van Kerrebroeck & Weiss, 1999]. However it is de¢ned, prevalence studies show that nocturia is reported to be a very common condition, a¡ecting particularly older age groups [Chute, 1993;Malmsten, 1997;Swithinbank, 1998]. …”
Section: (International Continence Society De¢nition From Ics Standarmentioning
confidence: 99%
“…A questionnaire-based study found the prevalence of nocturia increased from 56% in men > 45 years to nearly 90% of men ≥ 70 years [6]. In a recent meta-analysis, it was found that the majority of elderly men and women experience clinically significant nocturia: 29% to 59.3% in men and 28.3 to 61.5% in women aged ≥ 70 years experienced 2 or more voids per night.…”
Section: Epidemiologymentioning
confidence: 99%
“…частота НМ у мужчин значительно меньше, чем у женщин, и находится в пределах от 5 до 9 % [25,26]. Результаты большинства исследова-ний показали преобладание у мужчин ургентно-го НМ (40-80 %), далее по частоте идут смешан-ное НМ (10-30 %) и стрессовое НМ (менее 10 %) [25,27,28].…”
Section: статья посвящена эпидемиологии гиперактивного мочевого пузырunclassified